The tomb of the priests of Amun : burial assemblages in the Egyptian Museum of Florence - Sousa, Rogério, (Culture and History of the Ancient Near East, 2018)
The Tomb of the Priests of Amun, also known as Bab el-Gasus, was uncovered in 1891 at Deir el-Bahari (Thebes). The site proved to be the largest undisturbed tomb ever found in Egypt, as there were found the intact burials of 153 individuals that lived under the 21st Dynasty (ca. 1069-945 BC). This outstanding find was subsequently divided in lots of antiquities and dispersed by 17 nations. This volume presents the first comprehensive publication of the Italian Lot, kept in the Egyptian Museum of Florence. Besides the formal description of the objects, a critical assessment of the collection is provided regarding the reconstruction of the burial assemblages, the reuse of the burial equipment and the art historical examination of coffin decoration.